Effect of radix Salviae miltiorrhizae on the gene expression of nitric oxide synthase in ischemic rat brains - Wu, W; Kuang, P; Li, Z (Journal of traditional Chinese medicine, 1998)
The effect of Radix Salviae Miltiorrhizae (RSM) on the gene expression of nitric oxide synthase (NOS) in rat brains during ischemia was studied with in situ hybridization and the results were analyzed with IBAS 2000 Image Analysis System. It was found that NOS gene expression of cerebral cortex and caudate-putamen was markedly increased in 24 hours in ischemia group (P < 0.01). In RSM-treated rats, although the NOS gene expression of ischemic side was also increased as compared with contralateral cortex and caudate-putamen, it was significantly lower in RSM-treated rats than those of the controls (P < 0.05, P < 0.01). The present study indicates that RSM can partly inhibit NOS gene expression of cerebral cortex and caudate-putamen during ischemia. This may be one of the protective mechanisms of RSM on cerebral ischemia.